TRANSFORMING TRADITIONAL CUISINE INTO TECHNOPRENEURIAL INNOVATION: NASI TUTUG ONCOM (NTO) AS A GASTRONOMIC TOURISM ATTRACTION - Rahmat, Silvia Wijaya; Pramudya, Wisnu; Ramadhan, Danny Rizky; Annajam, Getar Jagat Raya Rahmatul; Millah, Riza Saepul (Smart Education, 2025)
Abstract: This study examines the potential of nasi tutug oncom (NTO), a traditional Sundanese dish from Tasikmalaya, as a culturally rich, digitally marketable gastronomic tourism product. Although Indonesian culinary heritage has gained attention in tourism development, regional dishes like NTO are understudied in both research and policy. The study aims to (1) analyze the attractiveness of NTO as a tourism product, (2) evaluate existing promotional efforts and challenges, and (3) propose technopreneurial strategies to enhance its digital sustainability and marketability. A qualitative approach was employed through semi-structured interviews and participant observation with ten key stakeholders, including tourism officials, gastronomy experts, NTO producers, entrepreneurs, and travel agent. Using the